Effect of different amount of water supply on plant growth performance of cucumis melo ( Var. cantalupensis) Grown under control environment using rice husk ash - Nur Ana Nasuha Binti Kamarudin (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Cucumis melo is an important crop from an economic perspective. Right amount of water supply to irrigate the Cucumis melo is crucial to get high and maximum crop yield. The different amount of water supply or treatment give effects towards the plant growth and this had being observed daily as the plant growth performance expressed through the data recorded and graph plotted. The treatments included supplying four different amount of water which were 250 ml, 500 ml, 650 ml and 750 ml. The amount of water supplied based on the percentage of the evapotranspiration (ET) of Cucumis melo var. Cantalupensis. Those treatments labelled as treatment 1 (T1), treatment 2 (T2), treatment 3 (T3), and treatment 4 (T4). Six parameters were chosen as to monitor the Cucumis melo growth performance. They were the height of internodes, plant height, stem diameter, number of leaf, leaf width and leaf length. The graph plotted showed that the plant growth increases and gave different pattern. Besides that, the effects of different treatment were also determined on overall plant growth performance through statistical analysis of ANOVA. ANOVA showed that there were significant difference on overall Cucumis melo growth performance which was the different water treatments effect the plant growth performance. The most optimum water requirement was assessed for the best plant growth performance. All the six plotted graphs based on selected parameters were observed and treatments were compared. Results showed that the treatment 2 with 500 ml give the best growth performance for Cucumis melo. In conclusion, the different amount of water supply effect differently towards the plant growth.